Sentinel lymph node mapping in tumors of the pancreatic body: preliminary report - Durczyński, Adam; Hogendorf, Piotr; Szymański, Dariusz; Grzelak, Piotr; Strzelczyk, Janusz (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study : Actual lymphatic drainage of pancreatic body neoplasms and the proper extent of lymphadenectomy remain unknown. The aim of the study was to define the exact lymphatic draining pattern using the dye mapping method. Material and methods: The study enrolled patients who were operated on for tumor of the pancreatic body in the Department of General and Transplant Surgery of the Medical University of Lodz during 2010, with injection of 1 ml of blue dye (Patent Blue, Guerbet) in the centre of the neoplasm and sentinel node identification. Radical surgical management included distal pancreatectomy, whereas gastrojejunal or triple bypass anastomoses were performed in irresectable cases. Results: The study group consisted of 13 patients with locally advanced tumors of the pancreatic body (T3 and T4, mean tumor size 4.9 cm). Lymphatic mapping was able to identify sentinel nodes in 5 of 13 cases (38.46%). A sentinel node was found in station 11p (3 cases) and 9 (1 case). Skip metastasis to the left gastric artery node (group 7) was noted. All identified sentinel nodes were metastatic; tumor deposits were confirmed in non-sentinel nodes as well. Conclusions: In advanced pancreatic body tumors feasibility of sentinel node navigation is considerably restricted. Further studies in smaller tumors using optimized newer markers may define the exact lymphatic draining pattern.